2014
DOI: 10.1002/alr.21377
|View full text |Cite
|
Sign up to set email alerts
|

When do the risks of repeated courses of corticosteroids exceed the risks of surgery?

Abstract: This represents the first rationalized evidence-based analysis for when surgery should be considered in place of repeated courses of oral corticosteroids. This threshold provides a guide for otolaryngologists to use when making clinical decisions with patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 21 publications
0
39
0
3
Order By: Relevance
“…Of note, CRSsNP patients were not included in the analysis. 733 Given the potential risks of systemic corticosteroids, clearer evidence addressing the use of corticosteroids in CRSsNP patients is crucial to balance these risks. No published studies exist to determine the benefit of oral corticosteroids alone in CRSsNP, other than 1 study addressing olfaction.…”
Section: Viie3 Crssnp Management: Oral Corticosteroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, CRSsNP patients were not included in the analysis. 733 Given the potential risks of systemic corticosteroids, clearer evidence addressing the use of corticosteroids in CRSsNP patients is crucial to balance these risks. No published studies exist to determine the benefit of oral corticosteroids alone in CRSsNP, other than 1 study addressing olfaction.…”
Section: Viie3 Crssnp Management: Oral Corticosteroidsmentioning
confidence: 99%
“…Finally, an evidence-based risk analysis of oral corticosteroid use in CRSwNP was performed by Leung et al 733 Using published complications rates, QoL changes, and costs, their analysis simulated the economic impact of adverse events from a Medicare patient perspective, societal perspective, and a universal healthcare perspective. This analysis found that a breakeven threshold favored surgery over medical therapy when CRSwNP patients required oral corticosteroids more than once every 2 years.…”
Section: Viiie3 Crswnp Management: Oral Corticosteroidsmentioning
confidence: 99%
“…Some are likely to experience complications of treatment including not only complications of surgery but also complications of ongoing medical management, for example long-term steroid exposure. 27 When we perform such an analysis we find that endoscopic sinus surgery costs less to produce more QALYs than the option of medical management alone. A sensitivity analysis concludes with 95% certainty that endoscopic sinus surgery is the more cost effective option.…”
Section: Lecturementioning
confidence: 96%
“…The analysis favoured surgery over medication when patients needed more than one course of oral steroids every 2 years, once a year if concomitant asthma was present, or twice yearly for patients with Samter's triad [54].…”
Section: Comparative Evidence Between Medical and Surgical Interventionsmentioning
confidence: 99%